Application of Analytical Hierarchy Process (AHP) in Material Selection Process for Automotive Bumper Fascia - A, Hambali; M.S, Izzati; A.A, Tajul; A.R, soufhwee; Roni Sahroni, Taufik (Universiti Teknikal Malaysia Melaka, 2012)
This paper presents the application of analytical hierarchy process (AHP) in evaluating and determining the most appropriate material for the automotive bumper fascia. Incorrect decision on material in the early of design process might cause product would be unsuccessful during the usage stage. To avoid this problem, the decision making tool namely analytical hierarchy process can be employed during the selection process. To illustrate the use of the AHP, bumper fascia was selected as a case study to show how AHP is able to determine the best decision. Thus, the paper presented the steps determining the best material using AHP. The results showed that Polyurethane (PUR) with 30% GFR is the most suitable material for automotive bumper fascia as it has the highest value at 0.199. This decision was verified by conducting other decision making tool namely MindDecider. The results showed that Polyurethane (PUR) with 30% GFR is the best material for automotive bumper fascia.